Raziskave o vplivu odprtega dostopa na citiranost znanstvenih del - Koler-Povh, Teja (Geodetski vestnik, 2012)
Open access is a well-established way of publishing research results. There are many studies investigating the influence of open access on visibility of articles and citation counts. In this study, an overview and analysis of bibliometric studies analysing the extent and speed of citation were prepared,with special emphasis on the impact of open access, separately for certain scientific disciplines. We also highlight other factors that mainly affect the increased visibility and, consequently, the increase of the total citation count. We found that in the future it will be necessary to standardize the methodology of studying the effects of open access on citations, before the hypothesis of a positive correlation between the number of citations and open access can be fully confirmed or refuted.
Keywords: citation count; citiranost; odprti dostop; open access; pregled objav; publication review; the impact on the citations; vidnost objav; visibility; vplivi na citiranost